Are non invasive predictors of esophageal varices reliable? - Savith, Akshatha; Bhumireddy, Sidhartha Naidu (International Journal of Research in Medical Sciences, 2019)
Background: One of the most serious complications of portal hypertension is the development of esophageal varices and variceal bleeding due to the rupture of varices. The purpose of the study was to assess the efficacy of various clinical and laboratory parameters in predicting the presence and severity of esophageal varices in cirrhotic patients. Methods: This is an observational cross-sectional study done in the department of medicine in Vydehi Institute of Medical Sciences, Bengaluru over a period of one year. Total of 76 patients above the age of 18years with the diagnosis of cirrhosis of any etiology were included. Multivariate Backward method was applied and Portal vein diameter, Platelet count, PT INR, FIB-4 score, APRI, AST/ALT ratio were included as predictors in the model. Results: No statistically significant correlation was found between platelet count, portal vein diameter, FIB 4 score, APRI, AST/ALT ratio and presence of esophageal varices. Conclusions: Present study showed that the non invasive markers such as platelet count, portal vein diameter, FIB 4 score, APRI and AST/ALT ratio are not reliable in predicting the presence of esophageal varices.